Pengaruh Pemanfaatan E-Channel dan Literasi Digital terhadap Tingkat Kepuasan Nasabah Bank Jatim Cabang Kraksaan - Dini Fitriani Ali; Rizki Febri Eka Pradani (Universitas Batanghari Jambi, 2026)
Digital transformation in the banking sector is driving banks to develop technology-based services to improve service quality and customer satisfaction. The success of implementing digital services is influenced not only by the quality of e-channels but also by customers’ level of digital literacy in effectively utilizing technology. This study aims to analyze the influence of e-channel usage and digital literacy on customer satisfaction levels at Bank Jatim’s Kraksaan Branch, both partially and simultaneously. The study employs a quantitative approach using an associative-causal research design. The study population consisted of 5,200 active JConnect users, with a sample of 371 respondents determined using the Slovin formula through simple random sampling. Data were collected via a questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that the use of e-channels has a positive and significant effect on customer satisfaction. Digital literacy also has a positive and significant impact on customer satisfaction. Furthermore, the simultaneous use of e-channels and digital literacy has been shown to have a positive and significant impact on customer satisfaction at Bank Jatim’s Kraksaan Branch. These findings indicate that improvements in the quality of digital services must be balanced with improvements in customer digital literacy so that the implementation of digital banking transformation can deliver an optimal service experience and enhance customer satisfaction.